Knowledge, attitudes and practices related to influenza illness and vaccination in children: Role of awareness campaigns in changing parents' attitudes toward influenza vaccination in Jordan. Issue 25 (31st May 2019) - Awad, Samah; Abdo, Nour; Yusef, Dawood; Jawarneh, Afnan; Babaa, Ahmad; Alwady, Deya'; Al-Bawayeh, Haitham; Kasrawi, Ismail; Amaireh, Mohamad; Obeidat, Motaz; Bany Amer, Nama'; Alonze, Saad
Highlights: The influenza vaccination rate in children is low in the Jordanian population. Health resources correlated most with the influenza vaccine uptake in children. The main reason for declining the influenza vaccine were the side effects. Awareness campaigns changed parents' attitudes toward the influenza vaccine. Abstract: Background: Influenza infection is associated with a significant health burden in children, especially in developing countries. The influenza vaccine is an important preventive strategy for flu illness. Aim of this study to assess knowledge, attitudes and practices (KAP) related to influenza illness and vaccination in children in the Jordanian population and to study the effect of awareness campaigns on changing the attitudes of parents toward vaccinating their children against influenza. Methods: A cross-sectional study was conducted among families visiting shopping malls and parks in November 2016. A questionnaire was administered via in-person interviews. Answers to KAP questions regarding influenza illness and vaccination were summed, with a total KAP score of 30. Facts about influenza illness and vaccination were explained to parents and provided in printed pamphlets. Results: There were 1241 respondents. 10.9% of participants had vaccinated their children during the last season 2015/2016. The mean KAP score (standard deviation) was 16.21 (4.61). People living in urban areas, with high monthly income >600 JD and healthcare workers had higher KAP scores than their counterparts. Compared to other sources of information about the influenza vaccine, health resources correlated most with vaccinating children. Awareness and educational pamphlets changed attitudes positively in 29% of parents who refused the influenza vaccine for their children. Conclusions: Awareness about influenza illness and vaccination is insufficient, and the coverage rate of influenza vaccination in children is low in the Jordanian population. Implementing public health policies is necessary to spread knowledge about influenza illness and vaccination and to promote the practice of receiving the influenza vaccine in children. Educational campaigns are helpful in changing the attitudes of parents toward vaccinating their children against the flu.